Decentralisation in Indonesia: The Impact on Local Health Programs - Hidayat, Muhammad Syamsu; Mahmood, Afzal; Moss, John (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2018)
Background: After more than a decade of implementation, the outcomes of decentralisation in Indonesia, particularly for the health sector are still obscure. Government health expenditure in a number of districts has increased considerably, but despite this health system performance to a large extent seems unaffected, calling into question how health stakeholders actually interpret local needs and how this interpretation can influence the consequent process for developing health programs. The main objective is to reveal the impact of decentralisation on health programs. Methods: In order to explore the complexity of the process, thirty-six stakeholders from eight different districts were interviewed, individually. These stakeholders consisted of representatives of the executive and legislative bodies, and the head of the district health office. Using purposive sampling, districts as the unit of analysis were selected on the basis of different degrees of fiscal strength and of urbanisation. The data were explored using framework approach. Results: One feature of decentralisation was the transfer of central government-that includes the discretion to develop and financing local initiative health programs to the local governments. However, the extent of health programs in each local government depends on factors such as local fiscal capacity, regulations, and the political process. In the case of Jamkesda, local fiscal capacity will determine the coverage and benefit of the health scheme that usually was supported by local regulations. However, the amount of local budget allocated for Jamkesda, relied greatly on the political process. The role of Jamkesda as a vote-getter for local politicians is significance, both in term of local commitment (budget allocation and regulation) and the sustainability of the program. Conclusion: Decentralisation has changed the development of local health program, nevertheless, the scope of local initiative health programs is determined by local fiscal capacity and the political process.